Kaixin-San improves Aβ-induced synaptic plasticity inhibition by affecting the expression of regulation proteins associated with postsynaptic AMPAR expression - Zhang, Bo; Wang, Meng-Lu; Huang, Shu-Ming; Cui, Yu; Li, Yan (Frontiers in Pharmacology, 2023)
Objective: To explore the mechanism underlying Kaixin-San (KXS) regulation of postsynaptic AMPA receptor (AMPAR) expression to mitigate the toxic effects of amyloid-β protein (Aβ). Methods: An animal model was established via intracerebroventricular injection of Aβ 1–42. Morris water maze test was conducted to evaluate learning and memory, while electrophysiological recording was conducted to assess the hippocampal long-term potentiation (LTP). Western blotting was used to detect the expression levels of hippocampal postsynaptic AMPAR and its regulatory proteins. Results: The time spent to find the platform was significantly prolonged, the number of mice crossing the target site was significantly reduced, and the maintenance of LTP was inhibited in the Aβ group than in the control group. In the Aβ/KXS group, the time taken to find the platform was significantly shortened and the number of mice crossing the target site was significantly increased than in the Aβ group; further, the inhibition of LTP induced by Aβ was reversed. The expression of GluR1, GluR2, ABP, GRIP1, NSF, pGluR1–Ser845 was upregulated, while that of pGluR2–Ser880 and PKC δ was downregulated in Aβ/KXS group. Conclusion: Increased expression of ABP, GRIP1, NSF, pGluR1–Ser845 and decreased expression pGluR2–Ser880 and PKC δ under the influence of KXS, followed by the upregulation of postsynaptic GluR1 and GluR2, alleviated the inhibition of LTP induced by Aβ. Ultimately, the memory function of model animals was improved by KXS. Our study provides novel insights into the mechanism underlying KXS mitigation of Aβ-induced synaptic plasticity inhibition and memory impairment by altering the levels of accessory proteins associated with AMPAR expression.